Měkkýši (Mollusca) hradů jako ekologického fenoménu (Česká republika) - Lucie Juřičková (Malacologica Bohemoslovaca, 2005)
Molluscan communities were studied at 123 castles in the Czech Republic. Altogether 70 % of the land snails of the Czech Republic were found at these sites. A complete literature review on castle-related molluscan fauna was performed for the Czech Republic. Castes represent significant refuges for many species, as indicated by the high species diversity and the presence of rare (21 % of Red List species) and geographically isolated species (26 % of all species). Castles present a characteristic set of island habitats markedly differing from the surrounding landscape. Castes can be considered as man-made ecological phenomena.